(untitled) (Journal of Parents and Teachers, 2014)
Autumn can make you want to discover its magic and take a break on a walk through the woods. For a good walk it is essential to choose a route, and you can consult guidebooks or magazine articles to do so. In addition to the number and ages of the walkers, you should take into account some elements of the landscape that can add a touch of beauty to the walk. It also requires a certain amount of preparation, such as getting to grips with the compass, locating the route on a map or talking about the importance of caring for nature.